2002
DOI: 10.1007/bf03030306
|View full text |Cite
|
Sign up to set email alerts
|

Response of antioxidant enzymes in rice (Oryza sauva L. cv. Dongjin) under mercury stress

Abstract: We studied the effects of different co~[et~bral~ns of mercury (0.0 to 100 !~t) o. growth and p~Uc efficiency in rice plants treated for 21 d. In addilJo., we invesl~ated how this metal affected Ihe malondtaidehy~ (MDA) content as well as lhe ~ of five ~ enzymes -superoxJde dimnutase (SOD), ascorbale peroxidase (APX), glutathione reductase (GR), guaiacol pemxidase (POD), and ratalase (CAT). ~c ef@~mcy (F,/Fm) and seedling growth decreased as the cancentrabon of H s was increased in the growth media. Plants also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…AOS include superoxide anion (02), the hydroxyl radical ( 9 OH), hydrogen peroxide (H202), and singlet oxygen (102). *Corresponding author; fax +82-55-758-5110 e-mail jjl@gshp.gsnu.ac.kr The increase in AOS, which are also produced during normal aerobic metabolism, seems to occur in response to all abiotic stresses, including chilling (Lee et al, 2004), heavy metal toxicity (Ali et al, 2002), drought (Smirnoff, 1993), and salt Gossett et al, 1996). Failure to quench or inactivate the AOS may lead to the degradation of macromolecules in cells as membrane lipids, proteins, and DNA (EIstner, 1982;Smirnoff, 1993).…”
mentioning
confidence: 99%
“…AOS include superoxide anion (02), the hydroxyl radical ( 9 OH), hydrogen peroxide (H202), and singlet oxygen (102). *Corresponding author; fax +82-55-758-5110 e-mail jjl@gshp.gsnu.ac.kr The increase in AOS, which are also produced during normal aerobic metabolism, seems to occur in response to all abiotic stresses, including chilling (Lee et al, 2004), heavy metal toxicity (Ali et al, 2002), drought (Smirnoff, 1993), and salt Gossett et al, 1996). Failure to quench or inactivate the AOS may lead to the degradation of macromolecules in cells as membrane lipids, proteins, and DNA (EIstner, 1982;Smirnoff, 1993).…”
mentioning
confidence: 99%
“…The measurement of MDA (Shi et al 2012a), the accumulation of soluble sugar and proline (Bates et al 1973;Chinard 1952;Watanabe et al 2000), and the activities of SOD and POD (Ali et al 2002) were as previously described.…”
Section: Activities Of Ros-scavenging Enzymes and Accumulation Of Solmentioning
confidence: 99%
“…As mercury is a toxic metal, many studies have shown that, especially in the form of Hg 2+ , it readily accumulates in plant roots, though there is a barrier to translocation from roots to shoots, and that it has high phytotoxicity compared with other heavy metals ( Munzuroglu & Geckil, 2002 ; Gautam et al, 2010 ). The phytotoxic effects of mercury include the following: reduction in plant growth and yield production, alterations in nutrient uptake and homeostasis, genotoxicity on genomic DNA molecule, elevated amounts of reactive oxygen species and membrane lipid peroxidation, changes in the integrity of bio-membranes, inhibition of plant photosynthesis, and perturbation of almost any function in which critical or non-protected proteins are involved due to mercury’s high affinity for sulphydryl groups ( Patra & Sharma, 2000 ; Ali, Chun & Lee, 2002 ; Patra et al, 2004 ; Israr et al, 2006 ; Eibaz et al, 2010 ; Malar et al, 2015a ; Malar et al, 2015b ; Wang et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%